HIDDEN PARTS OF SIR THOMAS MORE’S “UTOPIA” - Qosimova Saida Umidjon qizi; Khamitov Eldorbek Erkin o’g’li (Лучшие интеллектуальные исследования, 2024)
Thomas More’s “Utopia” stands as a seminal work of political philosophy and speculative fiction, offering a visionary critique of the societal norms and institutions prevalent in Renaissance Europe. Published in 1516 amidst social upheaval and religious turmoil, More’s text presents an alternative model of social organization through the depiction of an imaginary island society governed by principles of communal ownership, egalitarianism, and civic virtue.